Mobile Tower Battery Resources Monitoring System Based on Iot Using Codeigniter - Supriyadi (Institute of Computer Science (IOCS), 2022)
Monitoring is a condition or activity that is used to provide information about the cause of an action that is being carried out, to find out the condition of a tool or device we are required to monitor it all the time so that we can know what information is or has happened to the device. Monitoring using IoT-based technology is a solution to the problems we face. In this paper, the author makes a web using the CodeIgniter framework. The CodeIgniter is an open or open source application based on the PHP framework with the MVC model or also commonly called the Model View Controller which is used to build a dynamic website using PHP code. The conclusion that can be obtained from study of website development with codeigniter frameworks is: in developing web-based applications, designers need a framework to simplify the work process. In its development, many frameworks have been created with features that simplify the performance process of an application. The frameworks that will be analyzed in this research are Codeigniter, the test analysis uses Load Test with a file size of 3401 KB. The Codeigniter has a higher average time and speed. In the average time value, Codeigniter has a greater time. time from the first minute to the end of the test minute is set with 3 minutes of testing successful session per second 2.41 seconds, successful page per second 2.44 seconds Respontime per second 0.50.